Pengaruh Pemahaman Mengikut Yesus Menurut Matius 16:24 Terhadap Motivasi Menjadi Hamba Tuhan - Ririn Utari; Ruwi Hastuti; Sarah Andrianti (Sekolah Tinggi Teologi Simpson, 2021)
This study aims to determine how much influence the understanding of following Jesus according to the Gospel of Matthew 16:24 on the motivation for the call to be the Servant of God among students of STT Nusantara Salatiga. This research uses descriptive quantitative method. The results showed that there was a low influence between the understanding of following Jesus according to the Gospel of Matthew 16:24 on the motivation for the call to become servants of God in students of STT Nusantara Salatiga in 2018. This is indicated by the level of correlation which is only 0.222. The results of the regression analysis showed that the coefficient of determination was 22.2%, meaning that the motivation for the call to become God's servant for STT Nusantara Salatiga students in 2018 was influenced by 22.2% by the understanding of following Jesus according to the Gospel of Matthew 16: 24, the rest 77.8% was influenced by other factors. which the authors did not research. The existence of a gap between understanding and motivation is due to other factors that may also significantly influence motivation. ABSTRAKPenelitian ini bertujuan untuk mengetahui seberapa besar pengaruh pemahaman mengikut Yesus menurut Injil Matius 16:24 terhadap motivasi panggilan menjadi Hamba Tuhan pada mahasiswa STT Nusantara Salatiga. Penelitian ini menggunakan metode deskriptif kuantitatif. hasil penelitian menunjukkan bahwa adanya pengaruh yang rendah antara pemahaman mengikut Yesus menurut Injil Matius 16:24 terhadap motivasi panggilan nmenjadi hamba Tuhan pada mahasiswa STT Nusantara Salatiga tahun 2018. Hal ini ditunjukkan dengan tingkat korelasi yang hanya sebesar 0,222. Hasil analisis regresi menunjukkan bahwa koofisien determinasi sebesar 22,2%, artinya motivasi panggilan menjadi hamba Tuhan mahasiswa STT Nusantara Salatiga tahun 2018 dipengaruhi 22,2% oleh pemahaman mengikut Yesus menurut Injil Matius 16: 24, selebihnya 77,8% dipengaruhi oleh faktor lain yang tidak diteliti oleh penulis. Adanya kesenjangan antara pemahaman dengan motivasi disebabkan adanya factor-faktor lain yang mungkin secara signifikan juga mempengaruhi motivasi.